No Crumbs in Bed: A Nurse-Led Initiative for Mealtime Mobility - Marianna L Hoffmann (My University, 2025)
Introduction: Low physical activity among hospitalized patients significantly contributes to poor health outcomes, such as physical deconditioning, pressure ulcers, pneumonia, and increased mortality. This issue is especially concerning for older adults, who often spend over 90% of their hospital stays in sedentary states, frequently taking fewer than 1,000 steps daily. Design: This project utilized a quality improvement design, employing an iterative approach to implement and evaluate a nurse-led initiative aimed at increasing patient mobilization during mealtimes. Methods: The "No Crumbs in Bed" initiative was carried out in a specialized medical-surgical progressive care unit at a large regional medical center. The project aimed to implement a mealtime mobilization protocol, encouraging eligible patients to move from bed to a chair for all meals. The Institute for Healthcare Improvement (IHI) Model for Improvement, specifically its Plan-Do-Study-Act (PDSA) cycles, guided the implementation. Data on the documented times and frequency of patients moving from bed to a chair, along with daily Johns Hopkins Highest Level of Mobility (JH-HLM) goals and scores, were systematically collected from Epic electronic health record reports. Staff perception surveys were administered using REDCap for data collection and analysis. Results: The initiative successfully increased documented patient mobility from a 2024 baseline of 21% to 33% by April 2025, surpassing the project's target of 31%. While a high percentage of patients (ranging from 79% to 84%) consistently had a JH-HLM goal assessed at four or greater (indicating a goal of out-of-bed to chair or higher), the proportion of patients meeting this assessed goal remained between 45% and 50% throughout the project period. Pre-intervention surveys revealed a strong staff perception of the severity and likelihood of complications from immobility, while also highlighting significant barriers related to time constraints, patient factors, and staffing issues. Conclusion: This nurse-led initiative demonstrated that structured interventions can significantly improve patient mobility documentation within an acute care setting. Despite the identified barriers to consistently achieving assessed mobility goals, including inconsistent meal delivery, limited seating, and established cultural norms that favor bed rest, the project provides a practical framework for fostering a culture of mobility. This approach promises to improve long-term patient outcomes by reducing complications associated with immobility, aligning with the IHI’s Triple Aim framework and Healthy People 2030 goals. Clinical Relevance: This nurse-led initiative offers a practical framework for enhancing patient mobility during hospitalization, thereby reducing complications and promoting patient recovery through structured mealtime interventions. Keywords: mobility, hospitalization, nurse-led initiative, deconditioning, patient outcomes, Triple Aim, mealtime
Keywords: mobility, hospitalization, nurse-led initiative, deconditioning, patient outcomes, Triple Aim, mealtime